2022
DOI: 10.14309/ajg.0000000000001935
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Endoscopic Screening for Barrett's Esophagus in a Screening-Eligible Primary Care Population

Abstract: INTRODUCTION:Despite societal recommendations supporting Barrett's esophagus (BE) screening, it is unknown what proportion of eligible patients is screened in primary care. We assessed the proportion of BE screening- eligible patients evaluated in the primary care setting receiving upper esophagogastroduodenoscopy (EGD) and identified factors associated with undergoing EGD.METHODS:This was a retrospective study of BE screening-eligible patients, as defined by the American College of Gastroenterology's BE guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The development of NE-BE-EAC is a long process. 25 Although, BE is a precancerous lesion of EAC, not all BE will progress to EAC. Then, finding biomarkers that can predict whether BE will become cancerous or not has a very important diagnostic value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of NE-BE-EAC is a long process. 25 Although, BE is a precancerous lesion of EAC, not all BE will progress to EAC. Then, finding biomarkers that can predict whether BE will become cancerous or not has a very important diagnostic value.…”
Section: Resultsmentioning
confidence: 99%
“…There is growing evidence that the progression of BE to EAC is a multistep process that includes the development of non-developmental abnormal BE to low-grade atypical hyperplasia, then to high-grade atypical hyperplasia, and ultimately to EAC. [25][26][27] However, the molecular mechanism by which BE becomes cancerous is largely unknown. In BE is the only recognized precancerous lesion of EAC, and almost all EAC originates from BE.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Eluri et al (7) adds context to previous studies of EGD findings among patients referred for GERD, showing that those with symptoms refractory to therapy are not at increased risk of BE or erosive esophagitis, and atypical symptoms believed to be due to GERD, such as cough and globus, in addition to psychiatric distress may be inversely associated with finding esophageal pathology (8,9). Studying the referral patterns in a large primary care multipractice network, Eluri et al (7) demonstrated that, by and large, the patients being referred for EGD are the wrong ones if we are trying to address the burden of EAC. We are being sent patients with refractory symptoms (who are less likely to actually have GERD) or patients with alarm symptoms (who are unlikely to benefit from endoscopic therapy for early neoplastic lesions) rather than the patients with typical GERD symptoms who have responded to therapy.…”
mentioning
confidence: 99%
“…In this issue of the Red Journal, Eluri et al (7) performed a retrospective analysis of primary care patients within a multipractice network finding that only 39% of patients with GERD meeting guideline criteria for screening had undergone EGD. Only 9% of those were specifically referred for screening purposes.…”
mentioning
confidence: 99%
See 1 more Smart Citation